5th Meeting of the “Music and Minorities” Study Group: Prague, Czech Republic, May 24 – July 1, 2008. Organizers: Faculty of Humanities of Charles University, Prague, Ethnological Institute of the Academy of Science of the Czech Republic, Slovo 21. - Jurková, Zuzana (Lidé města, 2008)
The International Council for Traditional Music (ICTM, originally the International Folk Music Council) was founded in 1947 as the first major international ethnomusicological organization. In contrast to the Society for Ethnomusicology, which was founded eight years later and combines mainly American ethnomusicology with relatively closely-related scientific paradigms, ICTM is extremely diversified not only regarding scientific paradigms, but also in other directions. Its biennial world conferences are comprised of hundreds of participants who present in many parallel sessions (e.g., last year in Vienna there were usually six). They represent an exemplary fair of field resources rather than what the word itself refers to, i.e., discussions or exchange of knowledge of scholars in the same field.